2013
DOI: 10.1088/0004-637x/769/1/47
|View full text |Cite
|
Sign up to set email alerts
|

The Cycling of Material Between the Solar Corona and Chromosphere

Abstract: Observations of transition region emission lines reveal the presence of redshifts in lines formed from the top of the chromosphere up to temperatures of about 2.5 × 10 5 K and blueshifts for temperatures above that. However, it is doubtful that the apparent large downward flows in the lower transition region represents an emptying of the corona, so some mechanism must be responsible for maintaining the mass balance between the corona and the lower atmospheric layers. We use a three-dimensional magnetohydrodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 32 publications
3
25
1
Order By: Relevance
“…On the other hand, in contrast to what was speculated by Guerreiro et al (2013), we find no evidence for rapid heating to coronal temperatures shortly before the cooling phase sets in. Two minutes prior to t = 5000 s, the vast majority of the corks (i.e., 85%) already exist at temperatures above 100 000 K, while 4% are within the same temperature interval, whereas only 11% have lower temperature.…”
Section: Temperature Evolution Of Transition Region Corkscontrasting
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in contrast to what was speculated by Guerreiro et al (2013), we find no evidence for rapid heating to coronal temperatures shortly before the cooling phase sets in. Two minutes prior to t = 5000 s, the vast majority of the corks (i.e., 85%) already exist at temperatures above 100 000 K, while 4% are within the same temperature interval, whereas only 11% have lower temperature.…”
Section: Temperature Evolution Of Transition Region Corkscontrasting
confidence: 99%
“…Similar numbers are found for various other timesteps, suggesting a fast cooling process for the transition region corks once they reach the T = 100 000 K temperature range. Our results are in agreement with those of Guerreiro et al (2013) who injected a tracer fluid filling the volume between 20 000 K and 300 000 K into the Bifrost simulations. After two minutes of solar time, they found that 95% of the material has left this region, about 70% of which has cooled to chromospheric temperatures, while 25% of the material was heated to higher upper transition region or coronal temperatures.…”
Section: Temperature Evolution Of Transition Region Corkssupporting
confidence: 91%
See 1 more Smart Citation
“…IRIS contributes to our understanding by showing us in what form non-radiative energy is transmitted by the chromosphere into the corona. The studies described above help constrain wave-energy fluxes, while imaging of the chromosphere and photosphere combined with modeling constrains the forcing of the field into braids (see, e.g., Cirtain et al, 2013;Guerreiro, Hansteen, and De Pontieu, 2013) and twists by flows. IRIS also sheds light on how and where non-thermal energy is first released.…”
Section: Currents and Reconnectionmentioning
confidence: 99%
“…Hansteen et al (2010), for example, studied this mass and energy cycle between the lower atmosphere and the corona and found that both downflows and upflows are present at locations of (strong) magnetic field braiding, leading to redshifts and blueshifts of the order of about 5 km/s (see also e.g. Zacharias et al 2011;Guerreiro et al 2013). Observationally, a multitude of studies have found evidence for the presence of a complex interplay between upflows and downflows in the Transition Region (TR) and lower corona (e.g.…”
Section: Introductionmentioning
confidence: 99%